2015
DOI: 10.4314/jasem.v18i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Metric Distance Ranking Technique for Fuzzy Critical Path Analysis

Abstract: ABSTRACT:In this paper, fuzzy critical path analysis of a project network is carried out. Metric distance ranking technique is used to order fuzzy numbers during the forward and backward pass computations to obtain the earliest start, earliest finish, latest start and latest finish times of the project's activities. A numerical example is presented with a detailed step by step solution. The results of the numerical example presented are in agreement with published results in literature using other fuzzy rankin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Keeping these issues in mind, a study proposed that incorporating experts' opinions and the fuzzy Delphi method might be effective while using the PERT [15]. It is also suggested that uncertainty can be reduced by using experts' opinions to forecast the timeliness and cost estimations of activities in the form of fuzzy sets [72]. The scheduling results from the CPM and PERT were analyzed using a fuzzy method to improve scheduling in project management [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Keeping these issues in mind, a study proposed that incorporating experts' opinions and the fuzzy Delphi method might be effective while using the PERT [15]. It is also suggested that uncertainty can be reduced by using experts' opinions to forecast the timeliness and cost estimations of activities in the form of fuzzy sets [72]. The scheduling results from the CPM and PERT were analyzed using a fuzzy method to improve scheduling in project management [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The above distance measure describe the idea that more closer two fuzzy numbers be, more nearer are the truths of one being greater than or equal to the other. Definition 12 [40] The metric distance ranking technique was proposed by Chen and Cheng (2005) to order fuzzy numbers. Let two fuzzy numbers A and B be defined as follows:…”
Section: Definition: 11[22]mentioning
confidence: 99%
“…The results of the calculations are presented in the following tables. (19,20,21,30,39,47,48,49), (16,17,18,30,39,50,51,53), (13,14,15,30,39,54,55,56), (10,11,12,30,39,57,58,60), (7,8,9,30,39,61,62,63), (4,5,6,30,39,64,65 26, 27,29,36,37,38,39), (22,23,24,29,36,40,41,43), (19,20,21,29,36,…”
Section: Case 3: Solution Of Critical Path Problem Based On Generamentioning
confidence: 99%
“…48,50,61,62,64), (40,42,50,61,69,71), (37,39,50,61,72,75), (34,36,50,61,76,78), (31,33,50,61,79,82), (25,27,50,61,86,89))((0,0,0,37,45,55), (0,0,0,37,78,88), (0,0,0,37,93,106), (0,0,0,37,111,122), (0,0,0,37,127,139), (0,0,0,37,160,172)) C -D((25,27,29,36,37,39),(19,21,29,36,44,46),(16,18,29,36,47,50),(13,15,29,36,51,53),(10,12,29,36,54,57),(4,6,29,36,61,64)) ((0,0,0,28,39,51), (0,0,0,28,78,90), (0,0,0,28,96,111), (0,0,0,28,117,130), (0,0,0,28,136,150), (0,0,0,28,175,189)) B -E ((60,63,67,75,76,78), (54,56,67,75,83,86), (50,53,67,75,87,89), (47,49,67,75,91,93), (44,46,67,75,94,97), (38,40,67,75,101,104)) ((0,4,14,60,68,79), (0,0,14,60,102,112), (0,0,14,60,117,131), (0,0,14,60,136,147), (0,0,14,60,152,164), (0,0,14,60,185,197)) C -E ((66,68,70,78,79,81), (60,62,70,78,86,88), (57,59,70,78,89,92), (54,56,70,78,93,95), (51,53,70,78,96,99), (45,47,70,78,103,106)) ((2,12,22,67,75,85), (0,0,22,67,108,118), (0,0,22,67,123,136), (0,0,22,67,141,152), (0,0,22,67,157,169), (0,0,22,67,190,202)) D -E ((75,77,80,92,93,95), (69,71,80,92,100,102), (66,68,80,92,103,106), (63,65,80,92,107,110), (60,62,80,92,111,113), (54,56,80,92,118,120)) ((0,0,0,28,39,51), (0,0,0,28,78,90), (0,0,0,28,96,111), (0,0,0,28,117,130), (0,0,0,28,136,150), (0,0,0,28,175,189)) 22,95,293,319), (0,0,22,95,365,391)) ((0,0.03,0.06,0.24,0.29,0.35), (0,0,0.06,0.24,0.48,0.53), (0,0,0.06,0.24,0.56,0.63), (0,0,0.06,0.24,0.66,0.72), (0,0,0.06,0.24,0.75,0.82), (0,0,0.06,0.24,0.93,1)) A-C-D-E ((0,0,0,84,117,153), (0,0,0,84,234,270), (0,0,0,84,288,333), (0,0,0,84,351,390), (0,0,0,84,408,450), (0,0,0,84,525,567)) ((0,0,0,0.15,0.21,0.27), (0,0,0,0.15,0.41,0.48), (0,0,0,0.15,0.51,0.59), (0,0,0,0.15,0.62,0.69), (0,0,0,0.15,0.72,0.79), (0,0,0,0.15,0.93,1)) 0.268, R( ) = 0.245, R( ) = 0.198, R( ) =0.208 For = 0.5, R( ) = 0.273, R( ) = 0.261, R( ) = 0.238, R( ) =0.243 For = 0, R( ) = R( ) = R( ) = R( ) = 0.278 Here minimum ranks are 0.198, 0.238 and 0.278 for = 1, = 0.5 and = 0 respectively. So the critical path is A -C -D -E.…”
mentioning
confidence: 99%